2014
DOI: 10.1007/s00592-014-0617-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-23a, a potential biomarker for diagnosis of pre-diabetes and type 2 diabetes

Abstract: MicroRNAs (miRNAs) play a crucial role in the pathogenesis of type 2 diabetes (T2D); they regulate several metabolic pathways including insulin secretion, glucose homeostasis, so their potential as biomarkers of diagnosis and prognosis has became increasingly appreciated. In this study, we explore serum miRNA profiles in T2D patients. A total of ten candidate miRNAs were identified by Solexa sequencing scanning and followed by a stem-loop quantitative reverse transcription PCR (qRT-PCR) to assess these candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 36 publications
2
104
1
1
Order By: Relevance
“…The observation of the deregulation of miRNA profiles in different biological fluids of diabetic patients compared with healthy controls was the first evidence supporting the idea that miRNAs could be biomarkers of the diabetic disease (Table 1). Indeed, a differential miRNA profile between type 2 diabetic patients and healthy controls was found in whole blood [20,21], serum [22][23][24][25][26], plasma [27][28][29][30][31][32][33] and plasma exosomes [34]. Studies revealed a different miRNA pattern in serum of type 1 diabetic patients compared with healthy individuals [35], as well as in plasma [36,37] and urine [36].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…The observation of the deregulation of miRNA profiles in different biological fluids of diabetic patients compared with healthy controls was the first evidence supporting the idea that miRNAs could be biomarkers of the diabetic disease (Table 1). Indeed, a differential miRNA profile between type 2 diabetic patients and healthy controls was found in whole blood [20,21], serum [22][23][24][25][26], plasma [27][28][29][30][31][32][33] and plasma exosomes [34]. Studies revealed a different miRNA pattern in serum of type 1 diabetic patients compared with healthy individuals [35], as well as in plasma [36,37] and urine [36].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 99%
“…Interestingly, some reports show that the miRNA profile in plasma or serum is deregulated in the prediabetic state before the development of overt type 2 diabetes. Indeed, type 2 diabetic and prediabetic individuals have a differential profile of circulating miRNAs compared with controls [23,25,30,42]. Interestingly, for some miRNAs, such as miR-126 and miR23a, the difference was significantly greater in type 2 diabetic than in prediabetic individuals, suggesting that their levels could be correlated with the worsening of the glycaemic status [23,25].…”
Section: Circulating Mirnas As Early Predictive Biomarkers Of Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent study by Yang et al detected significantly lower levels of miR-23a in the serum of T2D patients compared to healthy controls that were already detectable in pre-diabetic individuals 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 [66]. A similar type of analysis was also performed in animal models to identify potential biomarkers predicting the development of T1D.…”
mentioning
confidence: 99%